Hubungan Higiene Sanitasi dengan Angka Kuman pada Piring di Warung Makan, Wirogunan, Kota Yogyakarta - Dyah Suryani; Piki Paslini; Suyitno (Yayasan Literasi Sains Indonesia, 2022)
Background: The practice of hygiene and sanitation of tableware starting from the washing process to improper storage can result in bacterial contamination of tableware. The purpose of this study was to determine the relationship between sanitation hygiene, utensil washing techniques and hand washing techniques with the number of germs on cutlery (plates) in a food stall in Wirogunan Village. Method: This type of research is quantitative with an analytical observational research design and a cross-sectional approach. The research sample was 31 ready-to-use glass plates at Indomie (Warmindo) food stalls. The sampling technique used was total sampling. The instrument used is a checklist sheet. Data analysis used Chi-square test and Fisher exact CI 95% (α = 0.05). Results: Chi-square test found that there was a relationship between the hygiene of the handlers (p-value = 0.001), the sanitation of the storage of cutlery (p-value = 0.049) the number of germs on cutlery (plates). On the other hand, the sanitation of the place (p-value = 0.586) was not correlated. The results of Fisher's test analysis showed that there was no relationship between utensil sanitation and the number of germs on cutlery (p-value = 0,600), utensil washing technique (p-value = 0,083), hand washing technique (p-value = 1,000) and the germ number of cutleries. (plate). Conclusion: There is a relationship between handler hygiene and storage sanitation with the number of germs on cutlery (plates) in a food stall, Wirogunan Village, Yogyakarta City.